Legal Protection for Customers in Electronic Goods Pawn-Deposit Agreements at PT Sarara Gadai Indonesia in Palu City - Rizky Sabrina; Rosnani Lakunna; Moh. Saleh (Faculty of Law, University of Dr. Soetomo, 2026)
Pawnshops play a strategic role in meeting the need for quick financing, especially for the general public and MSMEs that have limited access to formal banking services. Pawnshops in Indonesia that play a particularly strategic role are private pawnshops, which are regulated by OJK Regulation No. 31/POJK.05/2016 on the pawnshop business. One of the private pawnshops currently operating in Palu is PT. Sarara Gadai Indonesia; however, the pawn practices currently carried out by Sarara Gadai do not align with applicable laws, and the standard clauses in the agreements drafted by PT. Sarara Gadai Indonesia appears to be biased against the interests of consumers (customers). This study aims to examine how the pawn agreement for electronic goods is implemented at PT. Sarara Gadai Indonesia in Palu City, and to assess the compliance of the standard clauses in the pawn agreement for electronic goods at PT. Sarara Gadai Indonesia in Palu City, with the provisions of the Civil Code and OJK Regulation No. 31/POJK.05/2016. The research design employed is empirical legal research. The study was conducted at the PT. Sarara Gadai Indonesia branch is located at I Gusti Ngurah Rai. The results indicate that the implementation of electronic goods pawn agreements at PT. Sarara Gadai Indonesia constitutes a supplementary agreement to a debt-credit agreement, serving as collateral for debt repayment. In practice, the implementation of the agreement is supported by straightforward requirements, flexible payment terms, and a fast disbursement process. In terms of compliance, the clauses of the pawn agreement meet some of the legal requirements for pawn agreements, including the conditions for a valid agreement; however, they are not fully compliant because there are still several clauses that deviate from the legal provisions outlined in the Civil Code and the OJK Regulation.